KOREKSI ATMOSFER DATA LANDSAT-8 MENGGUNAKAN PARAMETER ATMOSFER DARI DATA MODIS - Muchsin, Fadila; Fibriawati, Liana; Rahayu, Mulia Inda; Hendayani, Hendayani; Pradhono, Kuncoro Adhi (Institut Teknologi Sepuluh Nopember, 2019)
Landsat-8 data (level 1T) received by user are still in digital number and can be used directly for mapping land use / land cover. However, the data still has low radiometric accuracy when it is used to derive information such as vegetation index, biomass, land use/ land cover classification, etc. so that it requires radiometric / atmospheric correction. In this study, we use the second simulation of a satellite signal in the solar spectrum (6S) method to eliminate atmospheric disturbance and compare the results with field measurements. The atmospheric parameters used were aerosol optical depth (AOD), water vapor column and ozone thickness from MODIS data with the date and time of acquisition are close to Landsat-8 data acquisition. From the analysis conducted on the values of vegetation index (NDVI, EVI, SAVI and MSAVI) surface reflectance shows that the vegetation index that has high accuracy is NDVI (3-11) % and the lowest is MSAVI (11-24) %. Analysis of the spectral response of atmospheric corrected image shows that visible band have good accuracy with RMSE values ranging from (1 - 4) %. On the contrary the lowest accuracy is found on the near infrared channel (NIR) with values (14-27) %.